Small and Innovative Molecules as New Strategy to Revert MDR - Zinzi, Laura; Capparelli, Elena; Cantore, Mariangela; Contino, Marialessandra; Leopoldo, Marcello; Colabufo, Nicola A. (Frontiers in Oncology, 2014)
MDR is a complex phenomenon principally due to the overexpression of some transmembrane proteins belonging to the ATP Binding Cassette (ABC) transporter family. Among these transporters, P-Glycoprotein (P-gp), is the mostly involved in MDR and its overexpression is the major cause of cancer therapy failure. The classical approach used to overcome MDR is the co-administration of a P-gp inhibitor and the classic antineoplastic drugs, although the results were often unsatisfactory. Different classes of P-gp ligands have been developed and, among them, Tariquidar has been extensively studied both in vitro and in vivo. Although Tariquidar has been considered for several years the lead compound for the development of P-gp inhibitors, recent studies demonstrated to be substrate and inhibitor, in dose-dependent manner. Moreover, Tariquidar SAR studies were difficult to carry out because of the complexity of the structure that do not allow to establish the role of each moiety for P-gp activity. For this purpose, SMALL molecules bearing different scaffolds such as tetralin, biphenyl, arylthiazole, furoxane, furazane have been developed. Many of these ligands have been tested both in in vitro assays and in in vivo PET studies. These preliminary evaluations lead to obtain a library of P-gp interacting agents useful to conjugate chemotherapeutic agents displaying reduced pharmacological activity and appropriate small molecules. These molecules could get over the limits due to the antineoplastic-P-gp inhibitor co-administration since pharmacokinetic and pharmacodynamic profiles are related to a dual innovative drug.